Youth participation in local process: reflections of Bangsamoro youth on policymaking in Malaysia - Salik, Datu Raid; Matucan, Rodolfo M. (Penerbit Universiti Kebangsaan Malaysia, 2023)
This note details our reflections on participating in an academic visit and learning exchange on public policymaking in Malaysia. The Institute of Public Policy and Management (INPUMA) at Universiti Malaya and The Bangsamoro Youth Commission (BYC) of the Bangsamoro Transition Authority jointly organised the program. Our executive summary covers the event and includes reflections from BYC participants participating in the program and policy lab simulation. We want to thank Professor Dr Khadijah Md Khalid and her team at INPUMA for their impactful and intellectual contributions to the event. During the program, we also considered Malaysia's history of the peace process in Mindanao and the cultural exchange between Malaysians and Bangsamoro. We are grateful to the professors and speakers who have enriched our public policy, governance, and youth development knowledge. INPUMA's commitment to empowering the BYC is commendable, and we appreciate all those who contributed to the program's success. We would like to recognise the BYC Coordinator and their team for their exceptional efforts in coordinating logistics and ensuring a successful learning exchange. Their professionalism and dedication ensured that everyone had a productive and enriching experience.